Optical properties of wurtzite/zinc-blende heterostructures in GaN nanowires - Jacopin, G.; Rigutti, L.; Largeau, L.; Fortuna, F.; Furtmayr, F.; Julien, F. H.; Eickhoff, Martin; Tchernycheva, M.; Justus Liebig University Giessen (My University, 2011)
The optical and structural properties of wurtzite GaN nanowires containing zinc-blende GaN inclusions of different thicknesses are investigated. Micro-photoluminescence spectra of single nanowires exhibit a series of narrow emission peaks with linewidth as low as 0.8 meV in the interval 3.1-3.42 eV. The peak energy blue-shifts with increasing excitation power following a similar to I(1/3) law due to the progressive band filling and to the screening of the internal field. The quantum confinement in these type-II crystal phase heterostructures was simulated in the framework of a one-dimensional effective mass model, accounting for the internal electrical polarization of the wurtzite GaN. The predicted transition energies are in good agreement with the energy statistics realized on more than 30 single nanowire emission spectra.
Keywords: wutzite GaN nanowires; zinc-blende GaN inclusions; microphotoluminescence spectra; transition energies; ddc:530